Faktor-Faktor yang Berpengaruh pada Kualitas Laba (Studi pada Sektor Perdagangan Besar/Grosir dan Kecil/Eceran dalam Bursa Efek Indonesia 2016-2018) - Heni Nurlailia; Deasy Ervina (JFAS : Journal of Finance and Accounting Studies, 2020)
Earnings quality provides an explanation related to the company's financial achievement, which in turn can be used as a basis for consideration by users of financial statements. A profit has a quality meaning if the company is able to use its operating cash inflows to finance the company's operating activities. This research is intended to examine the influence of earning quality factors. The type of research used is quantitative research. This study was conducted on the IDX by selecting the population in the large / wholesale and small / retail trade sector for the period 2016-2018. The sample obtained is 72. The required hypothesis testing is multiple linear regression. The research found that (1) profitability has no affect on earning quality, (2) liquidity affects on  earnings quality, (3) levareage has no affects on earning quality, and (4) also firmsize has no affects on earning quality.